Fracture Analysis of Butt Joint Girth Weld of Pipe and Flange. Issue 1 (1st December 2022) - Xu, Yan; Bi, Liuhan; Liu, Yinglai; Xu, Tianhan; Feng, Zhenjun; Bai, Qiang; Yang, Fengping
Abstract: Duplex stainless steel has been widely applied to industry. In this paper, nondestructive testing, chemical composition analysis, metallographic analysis, hardness test, and scanning electron microscope were used to study the causes of the crack in the butt joint girth weld of pipe and flange. Both steel pipe and flange are duplex stainless steel S31803. Through analysis, it was judged that the crack was a crystalline crack, generated in the welding process, which was related to the welding process and the control of the welding installation gap between the steel pipe and the flange with unequal wall thickness.